The Impact of Breast Care Nurses: An Evaluation of the McGrath Foundation's Breast Care Nurse Initiative - Jane Mahony; Holly Masters; James Townsend; Fionnuala Hagerty; Lisa Fodero; Joe Scuteri; Darren Doromal (Elsevier, 2019)
Objective: Over the four years to 30 June, 2017 the McGrath Foundation's Second Federal Government Breast Care Nurse (BCN) Initiative funded 57 McGrath BCNs (MBCNs) to deliver better continuity of care and provide specialized support to those diagnosed with and undergoing treatment for breast cancer. This article summarizes the findings generated through a mixed-method evaluation of the program's appropriateness, effectiveness, and efficiency. Methods: The evaluation comprised surveys and semi-structured interviews with patients, multidisciplinary clinicians and MBCNs. The research also drew on secondary materials, including MBCN activity and patient caseload data, a review of existing programs and costing information. Results: The evaluation generated evidence that access to an MBCN results in an improved experience for patients and clinicians, and that these impacts are more profound when MBCNs come into contact with their patients at the time of diagnosis. The economic modeling component of the evaluation revealed that there are cost savings to the health system when breast cancer patients have early access to an MBCN (through reduced health service utilization). The net saving produced by the program was estimated to be worth $6,323,257 per year, or $1,527 per new breast cancer patient seen. Stakeholders indicated that the MBCN model of care could be evolved to respond to emerging trends in breast cancer care pathways, such as a greater role in survivorship. Conclusion: This research advances the current understanding of the impact of BCNs on different levels of the health system and holds relevance for health-care funders, providers, and policy-makers. The evaluation demonstrates that access to an MBCN results in an improved experience for patients and clinicians, along with savings to the health system (through reduced health service utilization). The evaluation also shows that these impacts are more profound when MBCNs come into contact with their patients at the time of diagnosis.